2016
DOI: 10.3892/ijo.2016.3441
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA induces TRAIL sensitization of human lung cancer cells through selective ER stress induction

Abstract: Although tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is a promised anticancer medicine targeting only the tumor, most cancers show resistance to TRAIL-induced apoptosis. For this reason, new therapeutic strategies to overcome the TRAIL resistance are required for more effective tumor treatment. In the present study, potential of tanshinone IIA as a TRAIL sensitizer was evaluated in human non-small cell lung cancer (NSCLC) cells. NSCLC cells showed resistance to TRAIL-mediated cell death, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 57 publications
2
16
0
Order By: Relevance
“…Subsequent research further confirmed the anticancer effect of TNS on esophageal, prostate, colorectal, lung and GC (58). However, the mechanism by which TSN suppresses GC progression remains unclear.…”
Section: Introductionmentioning
confidence: 80%
“…Subsequent research further confirmed the anticancer effect of TNS on esophageal, prostate, colorectal, lung and GC (58). However, the mechanism by which TSN suppresses GC progression remains unclear.…”
Section: Introductionmentioning
confidence: 80%
“…Tanshinone IIA is the primary bioactive constituent of tanshinones [502], which has various pharmacological effects, including anti-inflammatory, anti-cancer and anti-atherosclerotic activities, and cardiovascular protection [503][504][505][506]. Tanshinone exhibits anti-cancer activities in stomach, prostate, lung, breast, and colon cancers, through inducing cell cycle arrest, apoptosis, autophagy, and inhibiting cell migration [507][508][509][510][511][512][513][514][515].…”
Section: Tanshinonesmentioning
confidence: 99%
“…Radix Salviae Miltiorrhizae, Rhizoma Chuanxiong , Radix Curcumae, and Rhizoma Curcumae promote blood circulation to remove blood stasis. Their extractions tanshinone, LI, and EI relieved RILI in vivo [38] and have antitumor effects against lung cancer [5456]. EI also enhances the radiosensitivity of lung adenocarcinoma [57].…”
Section: Discussionmentioning
confidence: 99%